Modelling the process of falling behind and its psychophysiological consequences. Issue 23 (19th October 2017) - Venhorst, Andreas; Micklewright, Dominic; Noakes, Timothy D
Abstract : Introduction: A preceding article investigated the psychophysiological responses to falling behind a performance matched opponent. The following temporally linked cause–effect relationships were hypothesised: falling behind precedes deterioration in valence, deterioration in valence precedes development of an action crisis, experience of an action crisis precedes psychoneuroendocrinological distress response and non-adaptive distress response reduces conduciveness to high performance, thereby preceding performance decrement. Methods: In this article, we applied structural equation modelling to test the extent to which the observed data fit the hypothesised cause–effect relationships. A five-step procedure was applied to model the interrelationships between the major study variables in the hypothesised temporal order. Results: Significant linear relationships were found between all hypothesised predictor and outcome variable pairs (p<0.024). The dynamic change in valence was a significant mediator (p=0.011) as it explained 35% of the relationship between falling behind and action crisis. All hypothesised cause–effect relationships continued to be significant after controlling for performance, descriptor, training and perceived strain variables. The observed data fitted the hypothesised structural model well with excellent model fit indices throughout. Conclusion: We applied, tested and confirmed the hypothesised debilitative psychophysiological processes that unfold in response to falling behind a performance matched opponent. The main findings were: deterioration in valence mediated the relationship between falling behind and action crisis, the mindset shift associated with an action crisis predicted increased blood cortisol concentrations and non-adaptive blood cortisol concentrations predicted performance decrement. The findings point towards the crucial role of affective and cognitive modifiers in centrally regulated and goal-directed exercise behaviour.